Peran Pondok Pesantren Ma'ahid Kota Kudus Jawa Tengah dalam Meluruskan Pemahaman Agama Islam Masyarakat Sesuai Al-Quran dan As-Sunnah Tahun 2015 - Nurmalasari, Dian; , Dr. Mutohharun Jinan, M.Ag; , Dr. Syamsul Hidayat, M.Ag (2016)
Kudus City is an area wich is historical and cultural sites, the potential of local cultures are numerous and diverse seems necessary to do a review for the religious leaders, particularly for institutions that have basic propaganda or symbols of Islam, namely the boarding school. Potential of diverse local culture, causing a lot evolved of tradition. for example; Bukak Luwur tradition, sacred the cows. Ma'ahid boarding schools to make efforts improve the quality of education in the understanding of religion straightening aqidah and forming character karimah . with efforts to serve a variety of activities and social religion routine. and periodic, such as Friday kliwon recitation, majlis mudzakaroh, program field preaching, program istisqa ', tadarus and I'tikaf, zakat and qurban. How Ma'ahid boarding school role in rectifying the understanding of Islamic communities that accord with the Quran and Sunnah, What are the factors supporting and hindering the implementation of activities in community undertaken by the Ma'ahid boarding school Kudus. This study was a qualitative research by describe the collected data as the scope of its research and field as a place of research (field research). The collected data is presented descriptively by using a sociological approach. Sources of data in this study were classified into two groups, namely primary data and secondary data were discussed in accordance with the objects in this study, that forms of Ma'ahid boarding school role towards the community. The data collected by using documentation, observation and interview collected data analyzed by qualitative analysis model then presented in a deductive conclusion. Based on the analysis, researchers concluded that shape the Ma'ahid boarding school Kudus in the form of religious activities and social with to purpose straighten the understanding of Islam is able to change the mindset and behavior in the public even in education, religious, economic, social and culture.